Leadership effectiveness in problem solving: A case study of Madrasas in Borneo - Khalifaturrahmah Khalifaturrahmah; Akhmad Maki; Sulaiman Sulaiman; Norsyam Amaly; Bidin Bidin; Rus'ansyah Rus'ansyah (TARBIYA: Journal of Education in Muslim Society, 2022)
AbstractThis Article is motivated by conflicts between the principal of the Madrasa and the teachers and education personnel in the Madrasa education unit. The general objective of this study is to gain an overview of the effectiveness of the principal of Madrasa’s leadership in solving problems in the Madrasa environment. This study examines the effectiveness of leadership in problem-solving for teachers and staff in Madrasas and identifies factors that influence problem-solving. The researcher used observation, interviews, and documentation methods to collect research data from teachers and education personnel and Madrasa managers at Madrasa Tsanawiya (MTs) An-Nur in Palangkaraya, State Madrasa Tsanawiya 2 (SMTs 2) in Banjar, and Madrasa Tsanawiya (MTs) Al-Kautsar in Tanah Bumbu in the academic year 2022-2023. The samples selected in this study were taken by purposive sampling, with a sample size of 12 people from each Madrasa. The principal of the Madrasa is responsible for empowering teachers and creating a harmonious Madrasa environment. Obstacles include a lack of collaboration and focus on student participation. Solutions include direct communication and involving stakeholders. The research provides recommendations for improving leadership effectiveness and problem-solving in Madrasas. Recommendations for the principal of Madrasas, teachers, education personnel, Madrasa committee and parents of students to improve the effectiveness of the principal of Madrasa’s leadership in solving problems in the Madrasa environment, creating a Madrasa environment that can support a student’s learning atmosphere.AbstrakArtikel ini dilatarbelakangi oleh konflik antara kepala Madrasa dengan para guru dan tenaga pendidik di unit pendidikan Madrasah. Tujuan umum dari penelitian ini adalah untuk mendapatkan gambaran tentang efektivitas kepemimpinan kepala Madrasah dalam menyelesaikan masalah di lingkungan Madrasah. Penelitian ini menguji efektivitas kepemimpinan dalam pemecahan masalah bagi para guru dan staf di Madrasah serta mengidentifikasi faktor-faktor yang mempengaruhi pemecahan masalah. Peneliti menggunakan metode observasi, wawancara, dan dokumentasi untuk mengumpulkan data penelitian dari para guru dan tenaga pendidik serta manajer Madrasah di Madrasah Tsanawiya (MTs) An-Nur di Palangkaraya, Madrasah Tsanawiya Negeri 2 (SMTs 2) di Banjar, dan Madrasah Tsanawiya (MTs) Al-Kautsar di Tanah Bumbu pada tahun akademik 2022-2023. Sampel yang dipilih dalam penelitian ini diambil melalui purposive sampling, dengan ukuran sampel sebanyak 12 orang dari setiap Madrasah. Kepala Madrasah bertanggung jawab untuk memberdayakan para guru dan menciptakan lingkungan Madrasah yang harmonis. Hambatan-hambatan meliputi kurangnya kerja sama dan fokus pada partisipasi siswa. Solusinya meliputi komunikasi langsung dan melibatkan para pemangku kepentingan. Penelitian ini memberikan rekomendasi untuk meningkatkan efektivitas kepemimpinan dan pemecahan masalah di Madrasah. Rekomendasi bagi kepala Madrasah, para guru, tenaga pendidik, komite Madrasah, dan orang tua siswa adalah untuk meningkatkan efektivitas kepemimpinan kepala Madrasah dalam menyelesaikan masalah di lingkungan Madrasah dan menciptakan lingkungan Madrasah yang dapat mendukung suasana pembelajaran siswa.